Effect of Leverage and Net Profit to the Firm Performance in Indonesia’s Small Medium Enterprises (SMEs) Listed Firms - Masyhuri, Muhammad (PT. Riset Press International, 2024)
Whether large corporations or small medium enterprises (SMEs), it is of utmost importance for all companies to achieve good firm’s performance in order to secure their existence in the economy, especially as publicly traded companies. The purpose of this study is to investigate the impact of firm’s leverage and net profit on the performance of listed SMEs in Indonesia. A total of 148 samples of secondary data used for this study were obtained from the Pefindo25 SME Index for companies listed on the Indonesian Stock Exchange from 2012 to 2017. The result shows that the two independent variables, the leverage and net profit, have a significant impact on the firm performance of SMEs, in opposite directions; the leverage variable has a negative significant impact on firm performance, while the variable net profit has a positive impact on firm performance.